Analysis of macroeconomic factors affecting poverty levels in Indonesia using a dummy regression model approach - Nur Rezky Safitriani; Valina Ambarwati; Miftahull Jannah; Nabila Safitri (Priviet Social Sciences Journal, 2025)
Poverty in Indonesia remains a complex macroeconomic issue, influenced by various social, economic, and regional disparities. This study employed a dummy variable regression model to analyze the factors affecting poverty more comprehensively, allowing for the identification of categorical geographic effects. This study examines the influence of the Gender Empowerment Index, Expected Years of Schooling, Gini Ratio, Open Unemployment Rate, and Formal Employment on the percentage of the poor population in Indonesia, while considering regional classifications in Western, Central, and Eastern Indonesia. The results show that the Gender Empowerment Index and proportion of Formal Employment have a significant negative effect on poverty, while the Gini Ratio has a significant positive effect. Additionally, the Western and Central regions exhibit significantly lower poverty rates than the eastern region. The dummy regression model explains 83,64% of the variation in poverty across provinces, making it a relevant basis for formulating region-specific and macro-economically informed poverty alleviation policies.